Why Similar Classroom Management Produces Different Student Engagement Outcomes in Islamic Schools? - Imelda Dwi Lestari; Sadam Fajar Shodiq (Bulletin of Educational Management and Innovation, 2025)
Background: Classroom management is widely recognised as a key factor influencing teaching effectiveness and student engagement. However, limited research has examined why similar classroom management strategies can yield different levels of student engagement within the same educational context. Purpose: This study aims to investigate the implementation of classroom management practices and explore the factors contributing to variations in student engagement in Indonesian Islamic secondary schools. Method: Using a qualitative case study design, data were collected through non-participant classroom observations conducted in four classes (IX B, VII F, VII E, and VII D) at SMP Muhammadiyah 1 Yogyakarta. Observations focused on classroom organisation, behaviour management, teacher-student interactions, and student participation in learning activities. Data were analysed using thematic analysis to identify recurring patterns and differences across the classrooms. Findings: The findings revealed that teachers applied relatively similar classroom management strategies in all observed classes, including structured classroom organisation, time management, instructional routines, and behaviour regulation. Despite these similarities, substantial differences emerged in the levels of student engagement. Class VII E demonstrated the highest level of engagement, characterised by active participation, positive behavioural responses, and frequent interaction with the teacher, whereas Class IX B and VII D showed lower levels of engagement, characterised by passive participation, indifference, and limited responsiveness. These findings further demonstrate that teacher-student interactions and student behavioural responses play a crucial role in shaping engagement outcomes and help explain why similar classroom management practices result in differing levels of engagement.